Features of the protection and preservation of Pulsatilla grandis Wender. (Ranunculaceae) in Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
The information on the protection and preservation of Pulsatilla grandis Wender. in Ukraine is given. Protection of species ex situ and in situ in Ukraine is analyzed. Found that species listed in international instruments and regional Red Book lists species that need protection at the local level in Ukraine and Europe. Despite that primary habitat of P. Grandis are faded, the area undergoes regressive changes, and its decline and fragmentation is observed. The disappearance of the species from the natural flora of Ukraine is due to anthropogenic influence. Found that P. grandis protection in Ukraine is insufficient. Type occurs in a small number of natural reserve fund. In Ukraine P. grandis is protected in nature reserve “Medobory”, in the National Park “Galician”, “Dniester Canyon”, “Karmelyukove Podillya”, “Kremenetsky mountains”, “Podilskii Tovtry”, “Northern Podillya”, “Hotinskaya”, a number of reserves (27) and natural monuments (6). Species is grown and propagated in 13 botanical gardens and 3 dendrological parks in Ukraine. To maintain and restore populations of P. grandis five botanical reserves of local importance, 1 botanical reserve of national importance, and one tract to be included in the zone of controlled recreation of Park “Podilski Tovtry”. In the future, of all the location P. grandis is offered to take under protection.
Keywords: Pulsatilla grandis, protection, conservation, Protected Areas, Ukraine.